Governanças híbridas no comércio justo citrícola entre o Brasil e a Europa: arranjos institucionais complementares aos contratos - Bouroullec, Melise Dantas Machado (Universidade Federal de São Carlos, 2010)
Focusing on hierarchy as an alternative to market, the New Institutional Economics (NIE) initially focused narrowly on the intermediary organizations. However, this situation started to change when Williamson (1985) stated that such intermediary transactions are the most common ones and denominated them hybrid governance in 1991. The studies carried out in the 80s and 90s enabled, among other factors, the distinction between hybrid governance and hierarchy resulting in an arousing interest in the development of contracts and the different coordination mechanisms in the field of NIE. More recently, some authors have highlighted the importance of studies on hybrid governance in the agricultural sector. Thus, the objective of this thesis is to indicate the existence of hybrid governance forms that complement the contract in transactions of supplying fair trade orange juice to the European market, as well as to point out the determining factors of this kind of governance. Therefore, the institutional environment of the agro-industrial fair trade is analyse, still poorly investigated in scientific studies in Brazil, and hybrid governance, considering the contributions of Ménard (1997, 2004) to the development of the concepts of NIE, were analyzed. Secondary data were considered and a field research was carried out both in Brazil and in Europe. Interviews were conducted with organizations of citrus farmers that are already inserted in the international citrus fruit fair trade, with export and import orange juice companies, and with some key agents. The analyses showed that orange juice supply transactions of the fair trade are administered by complex mechanisms that are more complex than contracts. Due to investments on human and brand name asset specificities, and the uncertainties related to the institutional environment of fair trande market, the contracts alone are not enough to conduct the transactions. Hence, coordination mechanisms, also known as mechanisms of adaptation are adopted based on two forms of private authority. On one hand, there is the authority performed by the certifying organization that constitutes a formal government. It establishes the norms and the production and trade standards in the fair trade of certified products, which leads to selecting the actors in the orange juice supply chain. The formal government also controls demands satisfaction rates and verifies whether the transactions are carried according to pre-established standards. In addition, it offers incentives to the adoption of organic citrus production and to long-term relationships. On the other hand, there is the informal authority: trust. Unlike the former, it is present in some cases and among some specific actors leading to a different way of selecting actors and controlling the factors that were not investigated by the formal government, such as the informal annual supply agreements between citrus farmers organizations and fair trade expert importers.
Keywords: Engenharia de produção; Governança; Comércio justo; Suco de laranja - comercialização; Confiança; Instituição ad hoc; Hybrid governance; Coordination mechanism; Formal government; Trust; Orange juice; Fair trade; ENGENHARIAS::ENGENHARIA DE PRODUCAO